Preface - Reiners, Torsten; Wood, L. (2015)
We have experienced a great deal of enjoyment while working towards bringing this volume to print and we hope that this sense of pleasure has been shared by the contributors to the work. It has been a time-consuming and arduous task from the first dissemination of the call for chapters to the final selection of interesting chapters demonstrating the influence and impact of gamification within business and education. We received lots of feedback and proposals for chapters, of which we had to pick those of the highest quality but also best fi t to tell a story of interest for the reader. The final selection came from a widely dispersed group of international authors—all experts with years of experience in research or practice—who discuss the current state-of-the-art in their areas of expertise and how they anticipate the development of gamification over the ensuing years. Before we send you off to immerse yourself in the book and enjoy your journey through the four parts (Theory, Education, Business, and Use Cases), you should get some insight into what you can expect.